The MENDORONG EFEKTIVITAS PELAYANAN JEMAAT DI GEREJA BETHEL (PENTAKOSTA) JEMAAT SION KEMIRI-SENTANI - Lewi Kabanga; Markus S. Gainau; Daniel Wenda; Amsi Talo (Jurnal PKM Setiadharma, 2022)
This perpetuation activity aims to help the congregation of God at Bethel Church (Pentecostal Church) Kecapi Sion, Kemiri-Sentani, resolve the causes of the worship vacuum that is often experienced. The method used in carrying out activities is divided into several parts: observation, IDI (In-depth Interview), core activities, and documentation/publication. The results of this community service activity show two causes of the worship vacuum experienced by the church, namely (1) natural conditions and (2) the inconsistency of the pastor. The alternative ways applied to prevent a worship vacuum are (1) The team made a banquet table that doubles to entertain church guests according to Papuan customs and to prevent stagnant water in the church hakam (2) The team will help the congregation by building connections and cooperation in providing services to this church.